The Correlation between English Department Students' Habit in Watching English Movies and Their Vocabulary Knowledge - Uena Apulisa; Novitri; Masyhur (English Study Program University of Pasir Pengaraian, 2021)
This research discussed the correlation between English department students' habit in watching English movies and their vocabulary knowledge. The background of conducting this research is to see how the possibility of students' habits in watching English movies influenced students' vocabulary knowledge. Furthermore, to find out if there is a significant correlation between English department students' habit in watching English movies and their vocabulary knowledge, this research determines the descriptive correlational method as the research design. After collecting and analyzing the data, it is obtained that the students' habit in watching English movies is categorized in the